Pre-harvest Interval and Pesticide Contamination in Different Vegetablescollected from Local Market of Vavuniya, Sri Lanka - Vijitharan, S.; Loganathan, P. (International Research Journal of Environmental Sciences, 2016)
Pesticides are designed to kill the pest and also it’s harmful to human. Synthetic pesticides not only pollute the environment but also persist in vegetables and passed through the food chain. The objective of this study was to identify theresidues by smell and appearance in different vegetables in Vavuniya local market, Sri Lanka. Ninety vegetable samples were randomly taken from Vavuniya local market and pesticide residue was analyzed by smell and their appearance. The collected data were analyzed using the descriptive statistics in SPSS (Statistical Package for Social Sciences). All farmers are depended on pesticides to control the pest. Eighty residue which was identified by smell and appearance. Around 60% of the farmers harvested their products within one week from the pesticide application and 36% of the farmers harvested after one week and around 4% of them harvested after two weeks from pesticide spraying. This survey is recommended to carry out awareness programs about indiscriminate use of pesticides and residual effects to farmers and consumers by government and other relevant institutions.
Keywords: Appearance; Pesticide contamination